2005
DOI: 10.1155/jbb.2005.287
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between PSMA and VEGF Expression as Markers for LNCaP Tumor Angiogenesis

Abstract: Our aim is the identification and correlation of changes in tumor-associated protein expression which results from therapy. LNCaP tumors, excised from nude mice treated either by orchiectomy or with the chemotherapeutic agent paclitaxel, were evaluated for the expression of proteins and receptors associated with growth, differentiation, and angiogenesis using immunohistologic procedures. Compared to untreated control tumors, both treatments reduced the expression of vascular endothelial growth factor (VEGF), p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
14
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 13 publications
4
14
0
1
Order By: Relevance
“…This is consistent with the prior observation of PSMA being expressed in the endothelial cells of certain solid tumor neovasculature, including prostate cancer, renal cell carcinoma, transitional cell carcinoma of the bladder, gastric cancer, and colorectal cancer (27–30). Also, a small study of LNCaP tumors grown in nude mice found a strong positive correlation between protein expression of PSMA and vascular endothelial growth factor, a signal protein that stimulates angiogenesis (40). …”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the prior observation of PSMA being expressed in the endothelial cells of certain solid tumor neovasculature, including prostate cancer, renal cell carcinoma, transitional cell carcinoma of the bladder, gastric cancer, and colorectal cancer (27–30). Also, a small study of LNCaP tumors grown in nude mice found a strong positive correlation between protein expression of PSMA and vascular endothelial growth factor, a signal protein that stimulates angiogenesis (40). …”
Section: Discussionmentioning
confidence: 99%
“…Several reports have indicated that PSMA expression, as opposed to other prostate-specific markers, is unchanged after taxane therapy in humans (32,33). For example, Kuroda et al found that androgen receptor and PSA levels were downregulated in a dose-dependent manner in response to docetaxel (33), possibly accounting for the higher PSA response rates (45%-50%) relative to the measurable response rates (8%-17%) in the 2 phase III trials that led the Food and Drug Administration to approve docetaxel in the treatment of prostate cancer (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…It is anchored to the cell membrane, which makes it an ideal promising therapeutic target (6,14). In addition, it can be internalized making it an appropriate candidate for pro-drug activity (6,14,22). In-vivo, anti-PSMA antibody has been used successfully against the neo-vasculature of a number of solid non-prostate tumors (6,23,24).…”
Section: Discussionmentioning
confidence: 99%
“…The VEGF is another angiogenic factor released by many tumor cells (22). Hypoxia promotes VEGF secretion (6) and VEGF simulates angiogenesis resulting in increased vascularity (22).…”
Section: Discussionmentioning
confidence: 99%